The Impact of Conceptual and Iʿrab Analysis of Verses 5-7 of Surah Al-Mu’minun on Traditional and Modern Tafsir Interpretations - Demirdöven, Doç. Dr. Necla Yasdıman (Journal of Ecohumanism, 2024)
In the traditional literature that is still in use, despite the verses encouraging the end of slavery, slavery has generally been seen as a permanent phenomenon, not a temporary one. These traditional views have continued to be effective in some modern periods and have resurfaced in wars in some parts of the world. This situation shows that some groups still use old books of jurisprudence as a reference to continue concubinage. Considering that the phenomenon of war can always occur, there is a danger of returning to old customs regarding female captives. Whether the dictionary and iʿrab analysis of the verses will allow this fatwa or not is one of the most important contributions to this field. The research has revealed that there is a significant difference between the classical and modern interpretations of the verses in question. Purpose: This study aims to evaluate the interpretations of classical and modern commentators through conceptual and iʿrab analysis of verses 5, 6 and 7 of Surah Al-Mu’minun. In particular, it focuses on the meaning of the phrase “mâ meleket eymânuhum” and reveals how traditional and contemporary interpretations of tafsir affect the meaning of the verses.Method: The research was conducted using conceptual analysis and linguistic analysis methods. First, the verses were conceptually analyzed and then analyzed within the framework of iʿrab, or Arabic grammar rules. Then, the interpretations of the commentators were examined to show the stages that our tafsir heritage has gone through in chronological order until today, and these interpretations were compared with the findings of the research.Main Findings: The study determined that there are serious differences in the meaning and scope of the phrase “mâ meleket eymânuhum”. The questions of whether the term "farc" in the verse refers to sexual intercourse or the protection of privacy, and whether the verse is addressed only to men or to both sexes, have been investigated. The research has also revealed significant differences between the classical and modern interpretations of verses 5-7 of Surah Al-Mu’minun. Innovation: This study has re-evaluated the concepts in the verses by focusing more on their literal meanings and the place of their iʿrab in the sentence. It has brought a new perspective to the field by analyzing the extent to which the Turkish translations are compatible with the research findings and interpretations.